Assessing Inflation Targeting after a Decade of World Experience - Vittorio Corbo; Oscar Landerretche; Klaus Schmidt-Hebbel (Oesterreichische Nationalbank (OeNB), 2001)
Ten years of inflation targeting worldwide provide valuable lessons. Inflation targeters (ITers) have been very successful in meeting their inflation targets (ITs). Industrial output sacrifice during inflation stabilization and industrial output volatility has frequently been lowered after IT adoption. ITers have consistently reduced inflation forecast errors after IT adoption. The influence of price and output shocks on the behavior of inflation and output gaps has changed much more strongly among ITers than in non-targeting industrial countries in the course of the 1990s. IT has played a role in strengthening the effect of forward-looking expectations on inflation, hence weakening the weight of past inflation inertia. Central bankers' aversion to inflation is on average not different among ITers in comparison to NITers but has risen in emerging-country ITers. ITers have gradually reaped a credibility gain, allowing them to achieve their targets with smaller changes in interest rates in the late 1990s than the changes that were required in the early 1990s.
Keywords: E52; E58; 330